Ativismo judicial: uma análise a partir do direito à moradia - Coutinho, Maria Laura de Souza (2010)
There was a significant change in the attitude of the Judiciary in Brazil after the promulgation of the current Constitution in 1988. Based on the Declaration of Rights, judges started to interfere in public policies and in legal relationships. This movement has caused some perplexity among the members of legal community. Some of them consider it as a threat to democratic values and popular sovereignty. Others, on the other hand, believe that this kind of judicial intervention is positive, because it makes possible to minorities to be heard and, as a result, contributes to the development of democracy. I believe that this movement is not completely understood. Moreover, I believe that we evaluate this kind of the intervention, analyzing judicial decisions only in some areas. I will try to demonstrate that we trust too much in the capacity of the Judiciary to give voice to minorities and others endangered groups. To make my point, I will observe how the Brazilian Judiciary decides demands for housing. These demands are important for three reasons. First, the lack of houses is a serious problem in Brazil. Second, in this demands we can see clearly how legal institutions can interfere in economic growth and social development. Finally, in this kind of demand, the dilemmas that modern judges face are more strikingly. In order to make my point, I will observe how the Supremo Tribunal Federal, the Superior Tribunal de Justiça and the Tribunal de Justiça de São Paulo, this last one responsible for judging the cases that happen in São Paulo, where the lack of houses is more dramatic, decide cases based on the right of housing, introduced in the Constitution in 2000. My conclusion is that judges rarely interfere in public policies in relation to housing.